Comparison of Two Gelatin and Thrombin Combination Hemostats in a Porcine Liver Abrasion Model. (1st June 2013) - Lewis, Kevin M.; Atlee, Holly D.; Mannone, Angela J.; Dwyer, Joseph; Lin, Lawrence; Goppelt, Andreas; Redl, Heinz
ABSTRACT Background: Surgical hemostasis is achieved using adjunctive hemostats when conventional methods fail. Objective: This study compares the effectiveness of two adjunctive gelatin-thrombin hemostats. Hypothesis: To determine effectiveness, hemostats were compared in vivo, in vitro, and using scanning electron microscopy (SEM). Methods: In vivo, a heparinized porcine liver abrasion model was used to compare hemostatic success, degree of bleeding, and blood loss at 2, 5, and 10 minutes post-treatment. In vitro, thrombin in the supernatant of each hemostat and Red Blood Cells (RBC'S) in the supernatant of clots formed by each was compared. Results: Ultrastructure of one gelatin was smooth and the other stellate. In vivo, smooth gelatin provided superior hemostatic success at 5 (85% vs. 60%; OR: 5.3; 95% CI: 1.66 to 17.9) and 10 mins (72.5% vs. 47.5%; OR: 5.0; 95% CI: 1.55 to 16.1). Smooth gelatin had a statistically different degree of bleeding at 5 (0.58 ± 0.87 [Mean ± SD] vs. 1.03 ± 1.12; OR: 3.36; 95% CI: 1.34 to 8.41) and 10 mins (1.13 ± 1.14 vs. 1.65 ± 1.05; OR: 3.87; 95% CI: 1.62 to 9.21). Mean blood loss was less with smooth gelatin at 2 (0.07 ± 0.19 vs. 0.13 ± 0.63 ml/min), 5 (0.04 ± 0.13 vs. 0.23 ± 0.45 ml/min), and 10 mins (0.09 ± 0.24 vs. 0.21 ± 0.32 ml/min). In vitro, supernatant of smooth gelatin had significantly less thrombin (6.81 vs. 10.9 IU/ml, p = .001), and significantly less RBC's than stellate gelatin (0.07 vs. 0.09 × 106/ul, p = .0085). Conclusion: Smooth gelatin has an increased ability to retain thrombin and RBC's in vitro which may explain why it provides superior hemostatic effectiveness, superior control of bleeding, and greater reduced blood loss in vivo.